1985
DOI: 10.5271/sjweh.2200
|View full text |Cite
|
Sign up to set email alerts
|

Work with video display terminals among office employees. I. Subjective symptoms and discomfort.

Abstract: KNAVE BO, WIBOM RI, VOSS M, HEDSTROM LD, BEROQVIST UOV: Work with video display terminals among office employees: I Subjective symptoms and discomfort. Scand J Work En viron Health II (1985) 457-466. Subjective symptoms and discomfort were evaluated by means of a questionnaire and compared between approximately 400 video display terminal (VDT) operator s and 150 selected referents . Previous and current illnesses, educational status, and smoking and drinkin g habits were also studied. The results showed the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0
8

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(110 citation statements)
references
References 2 publications
6
96
0
8
Order By: Relevance
“…A cross-sectional study found that the percent of workers reporting ''almost daily'' neck discomfort increased monotonically with increasing hours of daily VDT use 25) . Knave et al 26) reported a relationship between hours of VDT use per day and ''musculoskeletal complaints'' for women. Rossignol et al 27) found that individuals who had 7 or more hours of daily VDT use had a significantly elevated odds ratio for musculoskeletal complaints in comparison with nonusers.…”
Section: Workplace Factorsmentioning
confidence: 99%
“…A cross-sectional study found that the percent of workers reporting ''almost daily'' neck discomfort increased monotonically with increasing hours of daily VDT use 25) . Knave et al 26) reported a relationship between hours of VDT use per day and ''musculoskeletal complaints'' for women. Rossignol et al 27) found that individuals who had 7 or more hours of daily VDT use had a significantly elevated odds ratio for musculoskeletal complaints in comparison with nonusers.…”
Section: Workplace Factorsmentioning
confidence: 99%
“…Despite the relationship between visual symptoms and computer use (Bergqvist et al, 1992;Bergqvist and Knave, 1994;Dainoff et al, 1981;Knave et al, 1985;Mocci et al, 2001;Rocha and Debert-Riberiro, 2004), little intervention research exists demonstrating how best to design and build offices to reduce visual symptoms (Aaras et al, 1998(Aaras et al, , 2001Dainoff et al, 2005aDainoff et al, , 2005bHorgen et al, 2004Horgen et al, , 2005Konarska et al, 2005). The office ergonomic intervention literature contains few well-designed interventions (NRC, 2001;Brewer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Six studies (1-7), that were described in 7 papers, used physical examination or objective signs for the case definition and is below designated as «primary» studies. In the remaining fourteen studies (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), constituting the «secondary» studies, only selfreported symptoms were used for the case definitions (see Table 1). The table shows the documented relationships between certain exposures and one or several of the investigated upper limb disorders.…”
Section: Results Of Reviewmentioning
confidence: 99%
“…Twelve of the fourteen «secondary» studies have data on the amount of VDU use per workday. Four of these studies (9)(10)(11)14) identified an exposure-dose/ effect relationship between VDU work and symptoms. The symptoms concerned pain or numbness in wrist, hand or fingers and, for Knave et al, musculoskeletal symptoms in general.…”
Section: Vdu Work and Time Distribution Of Exposure (Table 1 Predictmentioning
confidence: 99%